Developmental regulation of G protein-gated inwardly-rectifying K(+) (GIRK/K(IR)3) channel subunits in the brain - Fernández-Alacid, Laura (2011)
G protein-gated inwardly-rectifying K(+) (GIRK/family 3 of inwardly-rectifying K(+)) channels are coupled to neurotransmitter action and can play important roles in modulating neuronal excitability. We investigated the temporal and spatial expression of GIRK1, GIRK2 and GIRK3 subunits in the developing and adult rodent brain using biochemical, immunohistochemical and immunoelectron microscopic techniques. At all ages analysed, the overall distribution patterns of GIRK1-3 were very similar, with high expression levels in the neocortex, cerebellum, hippocampus and thalamus. Focusing on the hippocampus, histoblotting and immunohistochemistry showed that GIRK1-3 protein levels increased with age, and this was accompanied by a shift in the subcellular localization of the subunits. Early in development (postnatal day 5), GIRK subunits were predominantly localized to the endoplasmic reticulum in the pyramidal cells, but by postnatal day 60 they were mostly found along the plasma membrane. During development, GIRK1 and GIRK2 were found primarily at postsynaptic sites, whereas GIRK3 was predominantly detected at presynaptic sites. In addition, GIRK1 and GIRK2 expression on the spine plasma membrane showed identical proximal-to-distal gradients that differed from GIRK3 distribution. Furthermore, although GIRK1 was never found within the postsynaptic density (PSD), the level of GIRK2 in the PSD progressively increased and GIRK3 did not change in the PSD during development. Together, these findings shed new light on the developmental regulation and subcellular diversity of neuronal GIRK channels, and support the contention that distinct subpopulations of GIRK channels exert separable influences on neuronal excitability. The ability to selectively target specific subpopulations of GIRK channels may prove effective in the treatment of disorders of excitability.